Prevalence and factors associated with dysglycemia in chronic obstructive pulmonary disease (COPD) patients with and without exacerbations / Khairil Khuzaini Zulkifli - Zulkifli, Khairil Khuzaini (2017)
Background and Aims: Dysglycemia, consisting of diabetes mellitus (DM), impaired glucose tolerance (IGT) and impaired fasting glucose (IFG), is a common comorbid of COPD. High prevalence of dysglycemia in COPD is well-recognized, however data comparing COPD exacerbation with incidence of dysglycemia is scarce. Thus, this study aimed to determine whether COPD exacerbation is a risk factor for dysglycemia. Materials and Methods: This is a cross-sectional study involving patients with established COPD aged 30 years and above (n=186) attending respiratory specialist clinics in UiTM campuses. Those on long-term corticosteroid therapy, active malignancy or in peripartum periods were excluded. Patients were divided into those with or without hospital admission for exacerbation in the past year. All participants had glycated hemoglobin level and inflammatory marker Interleukin-6 (IL-6) concentration assessment, and patients with no prior diagnosis of dysglycemia underwent oral glucose tolerance test (OGTT).